The seismic performance of tunnel-form buildings with a non-uniform in-plan mass distribution. (February 2021) - Mohsenian, Vahid; Nikkhoo, Ali; Rostamkalaee, Soheil; Moghadam, Abdolreza S.; Hejazi, Farzad
Abstract: The specific operating conditions in concrete box-type (tunnel-form) buildings would lead to the concentration of walls in the interior parts of the plan and lack of structural walls in the perimeter of the plan. In this situation, due to the considerable reduction in torsional stiffness, usually torsional vibration modes prevail over translational vibration modes, therefore the building behaves as a torsionally flexible structure. Torsionally flexible buildings are often more sensitive to the eccentricities of mass and stiffness as well as the intensity of the torsional component of an earthquake, in which, an increase in these parameters results in both increased forces and displacements. In this study, the effect of mass eccentricity in the plan on the behavior of box-type (tunnel-form) concrete buildings with 5 and 10 stories is scrutinized. The performance level of these buildings under the Design Basis Earthquake (475 years return period) for different values of mass eccentricity has been determined. In the framework of reliability studies, fragility curves were extracted based on the IM-Based method. Ratio estimation of the uncoupled frequencies for the studied models is another achievement of this research. The results prove that the studied system has high seismic reliability under torsions due to the asymmetric distribution of mass in the plan. In the studied buildings, while moving the center of mass up to 20% of the plan, there was no drop in performance level in Design Basis Earthquake (DBE) and all of the models stayed in the immediate occupancy performance level.